2022
DOI: 10.3390/biology11050735
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Fascial Reinforcement Development: From “a White Tablet” to a Sculpted Precise Organization by Movement

Abstract: Fasciae have received much attention in recent years due to their important role in proprioception and muscular force transmission, but few studies have focused on fetal fasciae development and there is no study on the retinacula. The latter are fascial reinforcements that play a key role in proprioception and motor coordination. Furthermore, it is still unclear if they are genetically determined or if they are defined by movements, and if they are present during gestation or if they appear only later in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…However, we did not observe the presence of an aponeurosis separating the TA and EDL. Furthermore, the posterior fascia of the deep posterior muscles was thicker in the fetus than in the adult and tended to decrease in thickness, as demonstrated in a previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 73%
“…However, we did not observe the presence of an aponeurosis separating the TA and EDL. Furthermore, the posterior fascia of the deep posterior muscles was thicker in the fetus than in the adult and tended to decrease in thickness, as demonstrated in a previous study [ 18 ].…”
Section: Discussionsupporting
confidence: 73%
“…We recently demonstrated that the fasciae during the fetal development are similar to “blank sheets” composed of few elastic fibers, abundant collagens and HA, on which various forces, fetal movements, loads and gravity, act to organize the tissue and the collagen fiber orientation [ 39 ]. At the same way, after birth and during life, the movements can structure the fascial system.…”
Section: Discussionmentioning
confidence: 99%
“…Ankle retinacula represent localized thickening of the deep fascia, which are structured during development, due to movement [31]. They serve to secure tendons in position during muscle contraction, permitting gliding between them [20].…”
Section: Discussionmentioning
confidence: 99%